2024
DOI: 10.1371/journal.pone.0300529
|View full text |Cite
|
Sign up to set email alerts
|

A single base pair substitution in zebrafish distinguishes between innate and acute startle behavior regulation

Elelbin A. Ortiz,
Philip D. Campbell,
Jessica C. Nelson
et al.

Abstract: Behavioral thresholds define the lowest stimulus intensities sufficient to elicit a behavioral response. Establishment of baseline behavioral thresholds during development is critical for proper responses throughout the animal’s life. Despite the relevance of such innate thresholds, the molecular mechanisms critical to establishing behavioral thresholds during development are not well understood. The acoustic startle response is a conserved behavior whose threshold is established during development yet is subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, combined exposure can cause more extensive damage. Ortiz et al found that anthropogenic damage to zebrafish brain tissue may alter their escape behavior [ 52 ]. Liao et al found that neuronal damage was observed in the brains of zebrafish after radiation, which eventually accounted for the behavioral variation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combined exposure can cause more extensive damage. Ortiz et al found that anthropogenic damage to zebrafish brain tissue may alter their escape behavior [ 52 ]. Liao et al found that neuronal damage was observed in the brains of zebrafish after radiation, which eventually accounted for the behavioral variation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%